2011
DOI: 10.1007/s11517-011-0803-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation for the suppression of pathological tremor

Abstract: Pathological tremor is manifested as an involuntary oscillation of one or more body parts. Tremor greatly decreases the quality of life and often prevents the patient from performing daily activities. We hypothesized that sensors-driven multichannel electrical stimulation could stabilize affected joints by activating the antagonistic muscles during involuntary activation of agonist muscles and vice versa (out-of-phase stimulation). Here, we present the new system (hardware and software) and the testing of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 17 publications
(25 reference statements)
0
43
0
4
Order By: Relevance
“…Such treatments, however, can be invasive, expensive, and may not produce effective, long-lasting tremor suppression tremor for all patients. As a potential alternative, studies have suggested the use of external devices to suppress tremor by mechanical loading (Pledgie et al, 2000; Rocon et al, 2007) or electrical stimulation (Javidan et al, 1992; Prochazka et al, 1992; Gillard et al, 1999; Popović Maneski et al, 2011; Gallego et al, 2013; Bó et al, 2014; Dosen et al, 2015). Although the efficacy of both methodologies has been proven, electrical stimulation arguably allows for a more compact and comfortable implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Such treatments, however, can be invasive, expensive, and may not produce effective, long-lasting tremor suppression tremor for all patients. As a potential alternative, studies have suggested the use of external devices to suppress tremor by mechanical loading (Pledgie et al, 2000; Rocon et al, 2007) or electrical stimulation (Javidan et al, 1992; Prochazka et al, 1992; Gillard et al, 1999; Popović Maneski et al, 2011; Gallego et al, 2013; Bó et al, 2014; Dosen et al, 2015). Although the efficacy of both methodologies has been proven, electrical stimulation arguably allows for a more compact and comfortable implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods with different sensors, including EMG [2,15,17,25,44], spirograms [7,37], and gyroscopes [23,32,38], have been used to quantify tremor. Accelerometers have been applied outside the operating room (OR) for a wide variety of purposes, e.g., to characterize pathological tremor [8,13], to compare it with physiological tremor [20,35,36], and to evaluate the severity and evolution of tremor [28,29,40] and the tremor-alleviating effect of drugs or DBS [22,36,47].…”
Section: Introductionmentioning
confidence: 99%
“…To verify amplifiers characteristics in the presence of the stimulation artifact, we used monophasic and biphasic stimulation pulses by the INTFES V1 electronic stimulator [22] and monophasic compensated pulse by the TremUNA stimulator [23].…”
Section: Testing Of the Novel Fast Recovery Emg Amplifiermentioning
confidence: 99%